Pengenalan Ekosistem Laut pada Siswa SMP Sekolah Dian Harapan Ambon - Pasanea, Krisye; Lokollo, Frijona F.; Supusepa, Junita; Haumahu, Sara; Rijoly, Frederik; Soukotta, Imanuel V.T.; Limmon, Gino V.; Rahman, Rahman (Pakis Journal Institute, 2025)
The introduction of marine ecosystems to school children, especially those in junior high school (SMP), plays an important role in environmental education. The aim of this service is to provide knowledge to Dian Harapan Middle School students regarding marine ecosystems and the various organisms that live in them. This community service activity at Dian Harapan Middle School will be held on Thursday, April 4 2024. This activity was attended by 149 students from classes 7A, 7B, 8A, 8B, 9A, and 9B. This service activity is carried out through several stages, namely licensing in the form of coordination with the school, preparation in the form of making presentation materials, implementation in the form of providing material about marine ecosystems, quizzes, introduction to biota samples and tools for measuring environmental parameters, evaluation in the form of pre-test and post-test answers. test and closing by holding a group photo session. Middle School students at Dian Harapan School are getting to know and know more about marine ecosystems, so it is important to preserve natural resources in the sea.